2007
DOI: 10.1192/bjp.bp.106.034942
|View full text |Cite
|
Sign up to set email alerts
|

Social exclusion and mental health

Abstract: Results We developed a model with five domains incorporating all the concepts relevant to social isolation in regular use in the mental health research literature. These five domains are: social network-quantity; social network-structure; social network-quality; appraisal of relationships emotional ; and appraisal of relationships-resources. We also identified well-developed measures suitable for assessing each of the five conceptual domains or covering multi-domains. Conclusions Our review proposes a conceptu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
97
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(101 citation statements)
references
References 34 publications
3
97
0
1
Order By: Relevance
“…A critical stance can be taken, exposing current discourses in a different light (Morgan et al 2007;Secker 2009). Parr, Philo, and Burns (2004) suggested that much of what was considered to be 'social inclusion' at the time was in fact about 'economic inclusion', as if the two were synonymous.…”
Section: Discussionmentioning
confidence: 99%
“…A critical stance can be taken, exposing current discourses in a different light (Morgan et al 2007;Secker 2009). Parr, Philo, and Burns (2004) suggested that much of what was considered to be 'social inclusion' at the time was in fact about 'economic inclusion', as if the two were synonymous.…”
Section: Discussionmentioning
confidence: 99%
“…Until now, no generally accepted and validated instrument has been developed to measure social exclusion in health research [3], [22]–[25], even though such an instrument is considered paramount to improve our understanding of how social exclusion influences health and health inequalities [2]–[4], [22], [26], [27]. The index discussed in this article is not only relevant for the Netherlands, but may be applied in other public health surveillance systems as well, such as the Centers for Disease Control and Prevention National Health Interview Survey [28], the Health Survey for England [29] and the Italian risk factor surveillance system PASSI [30].…”
Section: Discussionmentioning
confidence: 99%
“…Poor mental health may be both a cause and a consequence of social exclusion (Morgan, Burns, Fitzpatrick, Pinfold & Priebe, 2007; Payne, 2006; Social Exclusion Unit, 2004). However, most research has investigated social exclusion among people with common mental disorders such as depression and anxiety (Boardman, Currie, Killaspy & Mezey, 2010).…”
Section: Introductionmentioning
confidence: 99%